How citizen dialogue aligns with functional diversity in the development of urban areas - Eriksson, Hanna (My University, 2025)
This thesis explores how citizen dialogue aligns with the concept of functional diversity in the urban environment. Functional diversity in this study is defined based on Jane Jacobs's four criteria for city diversity, with additions from more recent sources. The four criteria’s are: a mix of primary functions, short blocks, housing diversity, and high population density A key assumption in this thesis is that a diverse group of participants in the dialogue process leads to more diverse and inclusive outcomes in urban development. Therefore, the study also examines strategies to achieve a broad and representative participation group. To answer these questions, three cases where citizen dialogue has been utilized were analyzed. The findings indicate that developing targeted engagement strategies is crucial for fostering diverse participation. Open invitations to dialogues were found to be less effective in achieving a diverse participation group; instead, collaboration with associations and councils proved more successful in reaching underrepresented groups. Regarding functional diversity, the study highlights that while citizen dialogue can foster support for a mix of functions, the majority of requests made by the dialogue participants were for secondary functions. The responsibility for ensuring a well-balanced distribution of primary and secondary functions ultimately lies with professionals to fulfil the requirement of a mix of primary functions. The findings also suggest that dialogue can influence urban form due to often being introduced early in the process. However, competing interests, such as demands for increased car infrastructure and walkability, may challenge functional diversity. Housing diversity was not a prominent topic in the analyzed dialogues. This further underscores the importance of including participants from different socioeconomic backgrounds. The study also found that concerns about density were common, yet through the use of models and visualizations, dialogues helped to generate support for higher-density solutions